Fiscal policy and equity the case of budgetary allocation to Mindanao regions - Andrada, Gian Carlo A.
The study primarily aimed to analyze the equitable distribution of financial resource allocated by the government to Mindanao regions. The use of the Theil index measurement of inequlity will quantify the differences of these allocations. The inequalities were measured in three ways: across regions, across sectors, and across the period of study coverage 91993-2002). Furthermore, the study also presented the trends of budget allocations to Mindanao regions. The study found out that the inequlaities across regions were mainly caused by the usual Region XI dominating pattern while other regions got a relatively lower budget. On the other hand, the high inequality of budget across sectors cabn be further explained by the large gap of the allocated budget for the education sector to the bottom list of the government's priorities, which are the science and technology, and the tourism sectors. The inequalities across period 1993 to 2002 were basically contributed by the significant shift of budget from fiscal year 1997 to 1998.